Detection of Breeding-Relevant Fruit Cracking and Fruit Firmness Quantitative Trait Loci in Sweet Cherry via Pedigree-Based and Genome-Wide Association Approaches - Crump, William Wesley; Peace, Cameron; Zhang, Zhiwu; McCord, Per (Frontiers in Plant Science, 2022)
Breeding for decreased fruit cracking incidence and increased fruit firmness in sweet cherry creates an attractive alternative to variable results from cultural management practices. DNA-informed breeding increases efficiency, yet upstream research is needed to identify genomic regions associated with trait variation of a breeding-relevant magnitude, as well as to identify parental sources of favorable alleles. The objectives of this research were to identify quantitative trait loci (QTLs) associated with fruit cracking incidence and firmness, estimate the effects of single nucleotide polymorphism (SNP) haplotypes at the detected QTLs, and identify ancestral source(s) of functional haplotypes. Fruit cracking incidence and firmness were evaluated for multiple years on 259 unselected seedlings representing 22 important breeding parents. Phenotypic data, in conjunction with genome-wide genotypic data from the RosBREED cherry 6K SNP array, were used in QTL analysis performed via Pedigree-Based Analysis using FlexQTL™ software, supplemented by a Genome-Wide Association Study using BLINK software. Haplotype analysis was conducted at QTLs to identify functional SNP haplotypes and estimate phenotypic effects, and haplotypes were tracked through the pedigree. Four QTLs (two per trait) were consistent across years and/or both analysis methods and validated previously reported QTLs. qCrack-LG1.1m (the label given to a consistent QTL for cracking incidence on chromosome 1) explained 2–15.1% of the phenotypic variance, while qCrack-LG5.1m, qFirm-LG1.2m, and qFirm-LG3.2m explained 7.6–13.8, 8.8–21.8, and 1.7–10.1% of the phenotypic variance, respectively. At each QTL, at least two SNP haplotypes had significant effects and were considered putative functional SNP haplotypes. Putative low-cracking SNP haplotypes were tracked to an unnamed parent of ‘Emperor Francis’ and ‘Schmidt’ and unnamed parents of ‘Napoleon’ and ‘Hedelfingen’, among others, and putative high-firmness haplotypes were tracked to an unnamed parent of ‘Emperor Francis’ and ‘Schmidt’, an unnamed grandparent of ‘Black Republican’, ‘Rube’, and an unknown parent of ‘Napoleon’. These four stable QTLs can now be targeted for DNA test development, with the goal of translating information discovered here into usable tools to aid in breeding decisions.